Evaluación de la incidencia de aflatoxinas en maíces de la sierra ecuatoriana - García Gavilánez, Margarita Susana (2020)
Aflatoxins are secondary chemical metabolites classified as contaminants in a number of foods and products. They are mainly produced by fungi Aspergillus spp. In Ecuador, there is not enough information that has allowed establishing with local data the maximum limits of aflatoxins G1, B1, G2 and B2 in dry grains of soft maize in the provinces of the Andean region; being that soft maize constitutes a basic food product in the highlands, and on the other hand, the affectation to health due to exposure to aflatoxins, can trigger chronic problems such as liver cancer. Thus, the objective of this study is to evaluate the incidence of aflatoxins in dry grains of maize (Zea mays) in the provinces of Azuay, Cotopaxi, Bolívar, Chimborazo, Pichincha, Carchi and Tungurahua. For this investigation, composite samples were taken in the indicated provinces, which were conditioned and analyzed in two laboratories to quantify aflatoxins (G1, B1, G2 and B2). As part of the study, the humidity data of the grain was determined in each sample at the time of conditioning. In the laboratory the water activity (Aw) was also determined and the fungi present with their percentage of infection were identified. The results indicated that the humidity of the corn grain in eleven composite samples (19-1364; 19-1363; 19-1362; 19-1361; 19-1360; 19-1359; 19-1358; 19-1357; 10; 11;12) met the specifications of the Ecuadorian standard that establishes a maximum of 13 percent. Regarding the presence of aflatoxins, the results indicates that there is no incidence of aflatoxins (G1, B1, G2 and B2) in any of the samples, all the reported values were below the sample limit of quantification (smaller than LC) of0,99; 0,93; 1,45 and 0,90 μg kg for G1, B1, G2 and B2 respectively, complying with the specification of international regulations that establish maximum limits of 4 μg kg. About the identification of fungi and the percentage of infection, four samples (19-1362; 19-1359; 19-1357; 19-1356) presented 100 percent infection, all with a higher presence of Aspergillus spp. that is the main producer of aflatoxins; a common feature in these samples (19-1362; 19-1359; 19-1357) with the highest infection is that they are soft shelled corn.